UV Radiation and Visible Light Induce hsp70 Gene Expression in the Antarctic Psychrophilic Ciliate Euplotes focardii - Lorenzo Fulgentini; Valerio Passini; Giuliano Colombetti; MICELI, Cristina; LA TERZA, Antonietta; Roberto Marangoni (Microbial Ecology, 2015)
The psychrophilic ciliate Euplotes focardii inhabits the shallow marine coastal sediments of Antarctica, where, over millions of years of evolution, it has reached a strict molecular adaptation to such a constant-temperature environment (about −2 °C). This long evolution at sub-zero temperatures has made E. focardii unable to respond to heat stress with the activation of its heat shock protein (hsp) 70 genes. These genes can, however, be expressed in response to other stresses, like the oxidative one, thus indicating that the molecular adaptation has exclusively altered the heat stress signaling pathways, while it has preserved hsp70 gene activation in response to other environmental stressors. Since radiative stress has proved to be affine to oxidative stress in several organisms, we investigated the capability of UV radiation to induce hsp70 transcription. E. focardii cell cultures were exposed to several different irradiation regimes, ranging from visible only to a mixture of visible, UV-A and UV-B. The irradiation values of each spectral band have been set to be comparable with those recorded in a typical Antarctic spring. Using Northern blot analysis, we measured the expression level of hsp70 immediately after irradiation (0-h-labeled samples), 1 h, and 2 h from the end of the irradiation. Surprisingly, our results showed that besides UV radiation, the visible light was also able to induce hsp70 expression in E. focardii. Moreover, spectrophotometric measurements have revealed no detectable endogenous pigments in E. focardii, making it difficult to propose a possible explanation for the visible light induction of its hsp70 genes. Further research is needed to conclusively clarify this point. Antonietta La Terza and Roberto Marangoni are joint last authors.